ANALISIS MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA (Studi Evaluasi Penanggulangan Kecelakaan Kerja Karyawan Pabrik Kelapa Sawit Rama Bakti Estate, Kec Tapung Hilir, Kab Kampar, Riau) - Gunawan, Arif Choirul; Andri, Seno (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
PT. Palm Oil Plantation Rama Bakti Estate is one of the units of the company headed by PT. SMART (Sinar Mas Agro Resources), which is located in Bringin Village Subdistrict Tapung Hilir, District Kampar, Riau Province. The company is engaged in the cultivation and processing of palm oil which made of Fresh Fruit Bunches (FFB) palm oil with multiple stages of processing that produces the final product in the from of Crude Palm Oil (CPO). PT Palm Oil Plantation Rama Bakti Estate also know as company that has a good reputation of doing the processing of palm oil. 2010-2013 But it is not in the line with K3 system which in not applied optimally. This impact on the high rates of work accident that accur in the company. Prevent accident companies to implement such programs more, leverageK3, K3 aplications, commitment and policys K3, the use personal protective equitment and make statistical reports of accident.The purpose of this research is to find out how the K3 management on the PT. Palm Oil Plantation Rama Bakti Estate which after being researched, it turns out that K3 management was good with score 2425 which is in the range (2060-2549). Therefore, the company expected to give more attention in making and implementing policies regarding K3, so work accident can be minimized and the employees can work more effectively and efficiently.Keywords: Management, K3